(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Microorganisms are known to bioremediate heavy metals and aromatic hydrocarbons of polluted sites, but there are only few reports of bioremediation of organotin contaminated sites. Little work has been done to explore the exact biochemical mechanism of organotin biodegradation and genes involved in the process. Five marine bacterial strains were selected from 128 isolates showing resistance to 0.1mM TBTC, among these, Alcaligenes sp. 2-6 (Strain S3) showing high level of resistance to 5mM TBTC have been extensively studied. Alcaligenes sp. 2-6 (strain S3) possesses a plasmid of 3.0 Kbps. However it has no role in TBTC degradation, since plasmid cured bacterial cells still showed TBTC resistance and degradation capability. The molecular biological and genetic studies have confirmed that the TBTC degradation gene is located on chromosome. The PCR analysis of genomic DNA revealed the presence of tbt ‘B’ gene of tbtABM operon indicating that, Alcaligenes sp. 2-6 is PCR +ve for this gene (1.42 kbps) which encodes a transporter protein belonging to RND family. This study has revealed that Alcaligenes sp. 2-6 (Strain S3) has great potential in the bioremediation of TBTC contaminated marine environment of coastal Goa.